Catalyzed and non-catalyzed synthesis of bioactive monastrol - Alvim, Haline Gerica de Oliveira (2014)
The bioactive 3,4-dihydropyrimidin-2(1H)-thione derivative known as Monastrol was synthesized under catalyzed and non-catalyzed conditions through the Biginelli multicomponent reaction under solvent-free conditions. The use of two Lewis acids (FeCl3 and CuCl2) and two Brønsted acids (HCl and CF3COOH) as catalysts improved the reaction yields of the transformation compared with the non-catalyzed reaction. The experiments investigated catalysis and its role, the importance of multicomponent reactions and their green features, and the application of these concepts to the synthesis of a biologically important structure.